Directory of exporters (Jamaica National Export Corporation Kingston 10JM, 1981)
Lists addresses of Jamaican Missions and Trade Commissions throughout the world. Classifies products exported from Jamaica according to the Brussels Tariff Nomenclature and lists companies exporting them. Alphabetically lists names and addresses of Jamaican exporting companies noting the products they export.
IDS